2004
DOI: 10.1177/0013124504264103
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring Equality of Educational Opportunity in the Digital Age

Abstract: As the quintessential right-to-education case, Brown v. Board of Education, Topeka, (1954) addressed equality of educational opportunity for all students regardless of race. Recently, the term digital divide has been used primarily to highlight inequities between various social groups with respect to acquiring computers and accessing the Internet. Given how use of these technologies has permeated our society, including our nation's schools, all relevant aspects of the digital divide must be addressed if the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…Teachers also targeted student access and use of computer technologies as an area of need. The majority of Ravine students are part of low socioeconomic status (SES) and minority populations; research has shown that most of these students do not have home access to up-to-date computers or Internet services (Bull, 2003;Gorski, 2002;Moghaddam & Nadezhda, 2004;Morse, 2004). Ravine teachers created JPD opportunities focused on classroom technology integration as a component of their work to improve instruction and combat the digital divide.…”
Section: Tpck For Impact: Classroom Teaching Practices That Promote Smentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers also targeted student access and use of computer technologies as an area of need. The majority of Ravine students are part of low socioeconomic status (SES) and minority populations; research has shown that most of these students do not have home access to up-to-date computers or Internet services (Bull, 2003;Gorski, 2002;Moghaddam & Nadezhda, 2004;Morse, 2004). Ravine teachers created JPD opportunities focused on classroom technology integration as a component of their work to improve instruction and combat the digital divide.…”
Section: Tpck For Impact: Classroom Teaching Practices That Promote Smentioning
confidence: 99%
“…Politicians, scholars, educational leaders, policy makers, and activists frequently employ this phrase when addressing issues of empowerment and democracy (Williams & Alkalimat, 2002). These discussions have identified various factors in identifying the digital divide phenomenon, including types of Internet or computer access (both quality and quantity), and available and/or actual uses of these technologies (Angus, Snyder, & Sutherland-Smith, 2003;Attewell, 2001;Moghaddam & Nadezhda, 2004;Morse, 2004;Solomon, 2002).…”
Section: Teaching For Social Justicementioning
confidence: 99%
“…However, in the short term, school and community programs can address the problem by creating access. Schools have the option to move to wireless Internet services and invest in laptops (Morse, 2004). While stopping short of giving each student their own computer, schools can provide enough laptops that multiple classes can use laptops simultaneously.…”
Section: Addressing Access and Digital Literacymentioning
confidence: 99%
“…Ninety-nine percent of non-White students reported owning a computer as compared to only 97% of White students in this study; these percentages are dramatic given the prior literature that suggests that non-White households are less likely to own a computer. Further research is needed to determine (a) if these patterns hold with other more heterogeneous populations; (b) once usage levels are similar between groups at one point in time, whether these remain this way across time or do larger societal structures affect the access and usage levels once individuals leave the relatively easy access present during their college careers; and (c) whether socialization experiences with technology are aimed at acquiring basic academic skills or enhancing problem-solving skills, given that these different functions may lead to different views of individuals' roles with regards to technology (Morse, 2004).…”
Section: Discussionmentioning
confidence: 99%